Differences among fathers, mothers, and teachers in symptom assessment of ADHD patients - Huang, Xia; Li, Hui-Qin; Simpson, Alan; Xu, Jia-Jun; Tang, Wan-Jie; Li, Yuan-Yuan (Frontiers in Psychiatry, 2023)
Background The Swanson Nolan, and Pelham scale version IV (SNAP-IV) is the most critical tool for ADHD screening and diagnosis, which has two scoring methods. ADHD requires symptom assessment in multiple scenarios, and parent and teacher reports are indispensable for diagnosing ADHD. But the differences of assessment results from fathers, mothers and teachers, and the consistency of results from different scoring methods are unknown. Therefore, we carried out this study to understand the differences in the scores of fathers, mothers and teachers using SNAP-IV for children with ADHD and to explore the differences in scoring results under different scoring methods. Methods The SNAP-IV scale and Demographics Questionnaire and Familiarity Index were used to survey fathers, mothers and head teachers. Measurement data are expressed as the mean ± standard deviation (x ± s). The enumeration data were described by frequency and percentage. ANOVA was used to compare group differences in mothers’, fathers’, and teachers’ mean SNAP-IV scores. The Bonferroni method was used for post hoc multiple comparison tests. Cochran’s Q test was used to compare the differences in the abnormal rate of SNAP-IV score results of mothers, fathers and teachers. Dunn’s test was used for post hoc multiple comparison tests. Results There were differences in scores among the three groups, and the differences showed inconsistent trends across the different subscales. Differences between groups were calculated again with familiarity as a control variable. The results showed the familiarity of parents and teachers with the patients did not affect the differences in their scores. The evaluation results were different under two assessment methods. Conclusion Results concluded that fathers did not appear to be an appropriate candidate for evaluation. When using the SNAP-V for assessment, it should be comprehensively considered from both the scorer and symptom dimensions.